After conviction - Goldfarb, Ronald R. (New York Simon and Schuster, 1973)
This book is about imprisonment of people, either innocent or murders. Some reforms of this sphere are proposed and as a result it caused many discussions. Nowadays the system of justice is very important in people lefe too.
Keywords: Law